Comparison of selenite F, Muller-Kauffmann tetrathionate and Rappaport's medium for salmonella isolation from chicken giblets after pre-enrichment in buffered peptone water. - Harvey, R. W. (Cambridge University Press, 1981)
Six hundred and eighty three samples of chicken giblets were examined for salmonellas. Three hundred and forty nine of these were neck and crop specimens and 224 were combined liver and heart samples. Two hundred and ten, in all, contained salmonellas. The technique of examination included pre-enrichment in buffered peptone water at 37 degrees C for 18 h and subculture to three enrichment media: Muller-Kauffmann tetrathionate, selenite F and Rappaport's magnesium chloride malachite green broth. Inocula from buffered peptone water to 10 ml of tetrathionate and selenite were 1 ml in each case. The inoculum from the pre-enrichment medium to 10 ml of Rappaport was 0.005 ml. Tetrathionate and selenite were incubated at 43 degrees C for 48 h. Rappaport's medium was incubated at 37 degrees C for 48 h. Subcultures from all three enrichment broths were made at 24 h and 48 h to brilliant green MacConkey agar. Selective agars were incubated at 37 degrees C for 24 h. The most successful technique for salmonella isolation used Rappaport's medium, which was significantly more efficient than either tetrathionate or selenite. This finding reinforces results obtained using sewage polluted natural water as test material and it is suggested that routine examination of environment samples for salmonellas could be based on Rappaport's medium alone. If S. typhi, S. dublin or subgenus III salmonellas were likely to be present in the sample, the technique described here would require modification.